Bioavailability and biochemical effects of diclofenac sodium 0.1% ophthalmic solution in the domestic chicken (Gallus gallus domesticus). (11th May 2016) - Griggs, Angela N.; Yaw, Taylor J.; Haynes, Joseph S.; Ben‐Shlomo, Gil; Tofflemire, Kyle L.; Allbaugh, Rachel A.
Abstract: Objective: To determine if topical ophthalmic diclofenac sodium 0.1% solution alters renal parameters in the domestic chicken, and to determine if the drug is detectable in plasma after topical ophthalmic administration. Animals: Thirty healthy domestic chickens. Procedures: Over 7 days, six birds were treated unilaterally with one drop of artificial tear solution (group 1), 12 birds were treated unilaterally (group 2) and 12 bilaterally (group 3) with diclofenac sodium 0.1% ophthalmic solution. Treatments were provided every 12 h in all groups. Pre‐ and post‐treatment plasma samples from all birds were evaluated for changes in albumin, total protein, and uric acid. Post‐treatment samples of all birds, collected 15 min post‐administration, were analyzed by high‐performance liquid chromatography with mass spectrometry for diclofenac sodium detection. A randomly selected renal sample from each group was submitted for histopathologic review. Results: Changes in pre‐ and post‐treatment plasma albumin were significant ( P < 0.05) in groups 2 and 3, but not for group 1. Pre‐ and post‐treatment changes in total protein and uric acid were not significant for any group. Diclofenac sodium was not detectable (limit of detection = 0.10 ng/mL) in plasma samples from birds in group 1. Post‐treatment concentration of diclofenac in group 3 was statistically greater than group 2 ( P = 0.0008). Histopathologic changes did not identify diclofenac‐induced acute renal tubular necrosis. Conclusions: Ophthalmic diclofenac sodium 0.1% administered topically every 12 h in one or both eyes for 7 days is detectable in systemic circulation in the domestic chicken, but does not cause overt significant changes in plasma uric acid or total protein.